THE ROLE OF METALANGUAGES İN FORMATİON OF COMPUTER SCİENCE TERMS (ON THE MATERIAL OF AZERBAIJANI AND FRENCH LANGUAGES) - Abdullayeva, K.R (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article is an attempt to draw attention to the involvement of different categories of languages to the formation of computer science terms. As a research material are used Azerbaijani and French languages. In the formation of computer science terms of these languages are highlighted following categories: the source language, national languages, compared languages, intermediary language, donor language, etymologically especially significant for this terminology languages, languages which serve as etymological basis for computer science terms of compared languages, languages serving as etymological basis for modern scientific languages. In research these categories are presented under the general concept of metalanguages. In reality they often overlap: the source language is at the same time national language, the categorie of compared languages also coincides with the categorie of national languages, intermediary language coincides in fact with donor language etc., however the proposed distinction finds it`s justification in terms of specific language material. Examples selected for illustration of each metalanguage also help to discover relations between the categories. The theoretical ground of the research are the statements about the role of latin and greek languages in formation of scientific terminologies of modern languages, semantic derivation as main way of transformation in terms of words and expressions of general use, the role of languages which had served as etymological basis for formation of lexical-semantic systems of national languages and therefore of scientific terminologies of those languages. In the article the attention is paid to the importance of French language in formation of computer science terminology of the source-language and other national languages. This role of French is also mentioned by J. Ourfahli in the investigation "Compared analyse of borrowed terms of informatics in Arab and French languages". As images which are in basis of formation of words and expressions are hidden in deep etymological layers the analyse may be useful for investigation of imagery of terms.